The effect of the Coefficient Function on the Solution Behavior for the Second-Order Complex Differential Equation - Alhily, Shatha S.; Saleh, Haneen Abbas (Iraqi Journal of Science, 2022)
The purpose of this research paper is to present the second-order homogeneous complex differential equation   , where   , which is defined on the certain complex domain depends on solution behavior. In order to demonstrate  the relationship between the solution of the second-order of the complex differential equation and its coefficient of function, by studying the solution in certain cases: a meromorphic function, a coefficient of function, and if the solution is considered to be a transformation with another complex solution. In addition, the solution has been provided as a power series with some  applications.